Patient-physician discrepancy in the perception of immune-mediated inflammatory diseases: rheumatoid arthritis, psoriatic arthritis and psoriasis. A qualitative systematic review of the literature. - José Antonio Sacristán; Tatiana Dilla; Silvia Díaz-Cerezo; Clara Gabás-Rivera; Susana Aceituno; Luis Lizán (PLoS ONE, 2020)
Introduction Recommendations on chronic diseases management emphasise the need to consider patient perspectives and shared decision-making. Discrepancies between patients and physicians' perspectives on treatment objectives, disease activity, preferences and treatment have been described for immune-mediate inflammatory diseases. These differences could result on patient dissatisfaction and negatively affect outcomes. Objective To describe the degree of patient-physician discrepancy in three chronic immune-mediated inflammatory diseases (rheumatoid arthritis [RA], psoriatic arthritis [PsA] and psoriasis [Ps]), identifying the main areas of discrepancy and possible predictor factors. Methods Qualitative systematic review of the available literature on patient and physician discrepancies in the management of RA, PsA and Ps. The search was performed in international (Medline/PubMed, Cochrane Library, ISI-WOK) and Spanish electronic databases (MEDES, IBECS), including papers published from April 1, 2008 to April 1, 2018, in English or Spanish, and conducted in European or North American populations. Study quality was assessed by the Oxford Centre for Evidence-Based Medicine criteria. Results A total of 21 studies were included (13 RA; 3 PsA; 4 Ps; 1 RA, Ps, and Axial Spondyloarthritis). A significant and heterogeneous degree of discrepancy between patients and physicians was found, regarding disease activity, treatment, clinical expectations, remission concept, and patient-physician relationship. In RA and PsA, studies were mainly focused on the evaluation of disease activity, which is perceived as higher from the patient's than the physician's perspective, with the discrepancy determined by factors such as patient's perception of pain and fatigue. In Ps, studies were focused on treatment satisfaction and patient-physician relationship, showing a lower degree of discrepancy in the satisfaction regarding these aspects. Conclusions There is a significant degree of patient-physician discrepancy regarding the management of RA, PA, and Ps, what can have a major impact on shared decision-making. Future research may help to show whether interventions considering discrepancy improve shared decision-making.